2014
DOI: 10.1001/jama.2014.839
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and Mortality Following Severe Cutaneous Adverse Reactions

Abstract: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are life-threatening conditions. Both primarily develop as idiosyncratic responses to drugs, 1 resulting in extensive epidermal detachment. Recurrence has been reported in isolated cases, and the overall risk of recurrence is unknown. Given the rarity of SJS and TEN, valid inferences about recurrence rates require the study of large populations over an extended period. We examined the long-term risk of recurrence following a first SJS or TEN e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 6 publications
(4 reference statements)
1
27
1
1
Order By: Relevance
“…who demonstrated that 42% of patients with SCAR were hospitalized with a subsequent episode of SJS or TEN. 108 Ex vivo diagnostics, such as T-cell enzyme linked immunospot (ELIspot) 109–116 and lymphocyte transformation testing (LTT), 94, 117120 and flow assays may improve the sensitivity and specificity of current testing and provide additional insights into immunopathogenesis. In some cases of appropriately selected phenotypes (MPE) and implicated antibiotics (penicillin or aminopenicillin), direct oral challenge without skin testing has been safely employed to exclude non-immediate hypersensitivity.…”
Section: Cross-reactivity and Cross-checking: The Importance Of Side Chmentioning
confidence: 99%
“…who demonstrated that 42% of patients with SCAR were hospitalized with a subsequent episode of SJS or TEN. 108 Ex vivo diagnostics, such as T-cell enzyme linked immunospot (ELIspot) 109–116 and lymphocyte transformation testing (LTT), 94, 117120 and flow assays may improve the sensitivity and specificity of current testing and provide additional insights into immunopathogenesis. In some cases of appropriately selected phenotypes (MPE) and implicated antibiotics (penicillin or aminopenicillin), direct oral challenge without skin testing has been safely employed to exclude non-immediate hypersensitivity.…”
Section: Cross-reactivity and Cross-checking: The Importance Of Side Chmentioning
confidence: 99%
“…At the same time, SJS-TEN overlap syndrome could not be separated by ICD-10. However, by using ICD-10 which has separate diagnostic codes for SJS and TEN, it reduces the risk of misclassification [26]. Second, we could not identify the causative agent for each case.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality is reported as 10% in Stevens-Johnson syndrome (SJS), 25-30% in toxic epidermal necrolysis (TEN), and 10% in drug hypersensitivity syndrome. 1,2 Among the drugs commonly causing SCARs, such as allopurinol, carbamazepine, phenytoin, phenobarbital, lamotrigine, abacavir, sulfonamides, and several nonsteroidal anti-inflammatory drugs, allopurinol is one of the most frequently involved causative agents of SCARs in many countries, including Korea. 3 Allopurinol, a xanthine oxidase inhibitor, is a urate-lowering agent prescribed frequently to patients with hyperuricemia or gout.…”
Section: Introductionmentioning
confidence: 99%